MRI abnormalities of the hippocampus and cavum septi pellucidi in females with schizotypal personality disorder - Dickey, Chandlee C.; McCarley, Robert W.; Xu, Mina L.; Seidman, Larry J.; Voglmaier, Martina M.; Niznikiewicz, Margaret A.; Connor, Erin; Shenton, Martha E. (Schizophrenia research, 2007)
This study examined MRI hippocampal volume and cavum septi pellucidi (CSP) in female subjects with schizotypal personality disorder (SPD) and comparison subjects. MRI was performed on 20 SPD and 29 comparison subjects with delineation of left and right hippocampi. Number of slices containing the CSP was counted. Subjects were given a working memory task, the Delayed Alternation task and other measures of working memory including the Wechsler Memory Test-Revised and the California Verbal Learning Test. Clinical measures were derived from the SCID-II. SPD females evinced bilaterally smaller hippocampal volumes compared with non-psychiatric female subjects (15.1% on left, 15.7% on right). Additionally, SPD subjects showed statistically significantly more slices containing CSP, and a trend level difference when large CSP was defined as four or more slices (20% vs. 6.9%). SPD subjects demonstrated more errors, more perseverations, and a trend toward more failure to maintain set on the Delayed Alternating task, which were associated with smaller left hippocampal volumes. There was no difference between groups in logical memory, verbal learning or semantic clustering nor a significant correlation between these measures and hippocampal volumes. Clinically, in SPD subjects, right hippocampal volumes correlated negatively with odd appearance/behavior and positively with suspiciousness/paranoia, and odd speech was positively correlated with the number of slices containing a CSP in exploratory analyses. Female SPD subjects showed bilaterally smaller hippocampal volumes and larger CSP than comparison subjects, similar to what has been shown in schizophrenia. Moreover, these abnormalities have clinically significant associations which may help to explain some of the manifestations of the disorder.